Model permainan“VOKIS” (Bola Voli Bulutangkis) dalam pembelajaran bola voli pada siswa kelas VII SMP Negeri 1 Bonang Kecamatan Bonang Kabupaten Demak (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
AbstracSocialization sport through school volleyball ternayata quite effective because volleyball is one of the games that can be learned and played by children basic unit level and college. Formulation of the problem of this research is how to model the game ”VOKIS” in learning volleyball penjasorkes class VII SMP Negeri 1 Bonang. The purpose of this study to produce a model of the game ”VOKIS” according to the characteristics of class VII SMP Negeri 1 Bonang Bonang District Demak easy for students to learn. The method of research is the development of a model refers to the development of Brog and Gall have been modified, namely: (1) conduct a preliminary and collection of information, including field observations and theoretical basis, (2) developing initial products, (3) evaluation by experts using a single expert and an expert penjas learning, and small group trials, using a questionnaire that is then analyzed, (4) revision of the product based on the results of expert evaluation and testing of small-scale (24 students), (5) field test (40 students ), (6) the results of the model game ”VOKIS” in learning volleyball penjasorkes class VII SMP Negeri 1 Bonang Bonang District Demak regency. Data such as the results of an assessment of the quality of products, suggestions for improvement of the product, and the results of questionnaires by students. The data analysis technique used is descriptive percentage to reveal the cognitive, affective and psychomotor students who have used the product. From the test results obtained by the expert evaluation data experts penjas 81% (good), a study 87% (good), a small test group 89.50% (excellent), and a field test 94.20% (excellent). From these results we concluded vokis game model in learning volleyball penjasorkes category, so it can be used in teaching students of class VII penjasorkes SMP Negeri 1 Bonang. Advice for teachers penjasorkes SMP Negeri 1 Bonang, can utilize this model of game development, so that the goal can be achieved with the maximum..